PENGARUH FINANCIAL TECHNOLOGY, TEKNOLOGI INFORMASI AKUNTANSI DAN MEDIA SOSIAL TERHADAP PENINGKATAN PENDAPATAN UMKM KOTA BATAM - Mesi Yury Anti Yury Anti; Argo Putra Prima (SCIENTIA JOURNAL, 2025)
The purpose of this study is to examine in depth how these three factors influence the increase in revenue of MSMEs in Batam City, both individually and collectively. This study used quantitative methods with primary data obtained from 100 MSME respondents in Batam City through questionnaires, as well as secondary data from official reports, journals, and books. Data analysis techniques included validity and reliability tests, descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, and hypothesis testing (t-test and F-test). The results indicate that fintech, accounting information technology, and social media, both partially and simultaneously, have a positive and significant effect on increasing MSME revenue in Batam City. This indicates that the better the utilization of these technologies, the greater the increase in MSME revenue